Configurable lipid membrane gradients quantify diffusion, phase separations and binding densities. Issue 42 (1st October 2015) - Liu, Katherine N.; Hung, Chen-min S.; Swift, Michael A.; Muñoz, Kristen A.; Cortez, Jose L.; Sanii, Babak
Abstract : Tunable collisions between spreading phospholipid membranes form functional gradients. Abstract : Single-experiment analysis of phospholipid compositional gradients reveals diffusion coefficients, phase separation parameters, and binding densities as a function of localized lipid mixture. Compositional gradients are formed by directed self assembly where rapid-prototyping techniques ( i.e., additive manufacturing or laser-cutting) prescribe lipid geometries that self-spread, heal and mix by diffusion.